Molecular identification of bacteria isolated from culture medium of rotifer fed on fishery waste diet - Stenly Wullur; HATOPAN NAPITUPULU; LETHA LOISE WANTANIA; ELVY LIKE GINTING; VEIBE WAROUW; SANDRA TILAAR; TRINA EKAWATI TALLEI; INNEKE FENNY MELKE RUMENGAN (Society for Indonesian Biodiversity, 2020)
Abstract. Wullur S, Napitupulu H, Wantania LL, Ginting EL, Warouw V, Tallei TE, Rumengan IFM. 2020. Molecular identification of bacteria isolated from culture medium of rotifer fed on fishery waste diet. Biodiversitas 21: 2735-2740. The aim of this study was 16S-rRNA sequences based molecular identification of bacteria isolated from culture medium of rotifer fed with fishery waste diet (FWD). We cultured rotifer Brachionus rotundiformis in sterilized seawater (salinity 25 ppt) using FWD, following the procedure in Patent No. P00201609066. Bacteria from the culture were collected, homogenized, diluted 10 to 1000 fold, spread on agar plates and incubated at 370C for 24 to 48 hours. Representative colonies of the bacteria according to their morphologies were isolated for further characterization. Genomic DNA of the isolates were extracted, and the 16S rRNA gene of the isolates were amplified. Polymerase Chain Reaction (PCR) product of each isolate was sequenced and queried against the NCBI GenBank database. Six different isolates based on size, color, elevation, margin, and colony were observed during 24-48 hours incubation at 370C. The 16S rRNA genes of the six isolates were successfully amplified and produced DNA band at 1300-1500 bp, with quality value equal to or greater than 20 (QV20+) of each entire sequence around 941-1253 bases. Basic Local Alignment Search Tool (BLAST) queries in the NCBI GenBank and EzBioCloud database using the 16S-rRNA gene sequences showed that the six isolates belong to four different genera, i.e: Bacillus, Staphylococcus, Vibrio, and Alteromonas.